2018
DOI: 10.3390/catal8050212
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructured Oxides Synthesised via scCO2-Assisted Sol-Gel Methods and Their Application in Catalysis

Abstract: Nanostructured metal oxides and silicates are increasingly applied in catalysis, either as supports or as active species in heterogeneous catalysts, owing to the physicochemical properties that typically distinguish them from bulk oxides, such as higher surface area and a larger fraction of coordinatively unsaturated sites at their surface. Among the different synthetic routes for preparing these oxides, sol-gel is a relatively facile and efficient method. The use of supercritical CO 2 (scCO 2) in the sol-gel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 106 publications
0
6
0
Order By: Relevance
“…Compared to RESS, several efforts have been dedicated to applying the SAS approach extensively towards the fabrication of various inorganic-based nanoarchitectures. In a case, Miedziak and coworkers fabricated the nanocrystalline cerium oxide (CeO 2 ) supported gold-palladium alloy catalysts utilizing the widely applied SAS method [ 47 ]. Compared to the products obtained from the conventional preparation techniques, this unconventional SCF-assisted SAS process resulted in the lesser polluting components with higher active oxidation catalytic performance.…”
Section: Preparation Of Diverse Inorganic-based Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to RESS, several efforts have been dedicated to applying the SAS approach extensively towards the fabrication of various inorganic-based nanoarchitectures. In a case, Miedziak and coworkers fabricated the nanocrystalline cerium oxide (CeO 2 ) supported gold-palladium alloy catalysts utilizing the widely applied SAS method [ 47 ]. Compared to the products obtained from the conventional preparation techniques, this unconventional SCF-assisted SAS process resulted in the lesser polluting components with higher active oxidation catalytic performance.…”
Section: Preparation Of Diverse Inorganic-based Materialsmentioning
confidence: 99%
“…Indeed, scCO 2 offers comprehensively distinctive properties, which can be explicitly used to synthesize and activate new types of materials, such as aerogels (metal or metal oxide aerogel, some polymer aerogels, aerogels particles) [ 47 , 69 , 76 , 98 , 99 ]. The process of sol-gel-based synthesis generally begins with the formation of a pseudo-solution through a hydrolysis and condensation reaction by blending some chemically active precursors.…”
Section: Preparation Of Diverse Inorganic-based Materialsmentioning
confidence: 99%
“…The sol-gel preparations are based on the formation of a colloidal solution (sol), obtained by hydrolysis and condensation of the soluble precursors, such as metallic, organometallic or alkoxides precursors [26]. Upon further condensation, the sol gives rise to an integrated network (gel), containing solvent molecules trapped, finally the gel can be converted to solid material by removing the solvent through drying and/or thermal treatments [27,28]. Films of variable thicknesses can be realized by dip-coating or spin-coating of the structures, making this technique effective and not expensive.…”
Section: Coating Techniquesmentioning
confidence: 99%
“…In addition, scCO 2 has high diffusivity and extremely low surface tension, which are very important for maximum preservation of the formed nanostructures when removing CO 2 from the system, which can be achieved simply by depressurisation. 35 It has been extensively reported that the formation of nanomaterials typically proceeds differently with the assistance of scCO 2 . [36][37][38] Further advantages of the use of scCO 2 as a reaction medium include the low toxicity and low cost of carbon dioxide and the relatively mild conditions needed to achieve its supercritical point (T c = 31.1°C, p c = 73.9 bar).…”
Section: Introductionmentioning
confidence: 99%